2009
DOI: 10.1111/j.1467-6419.2008.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Offshoring, Multinationals and Labour Market: A Review of the Empirical Literature

Abstract: Abstract. This paper reviews the empirical literature on the effects of offshoring and foreign activities of multinational enterprises on developed countries' labour markets. Results suggest that material offshoring worsens wage inequality between skilled and unskilled workers; it also seems to make employment more volatile, by raising the elasticity of labour demand and the risk of job losses. Service offshoring exerts at most small negative effects on total employment, and changes the composition of the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 228 publications
(279 reference statements)
9
141
1
5
Order By: Relevance
“…Business and management science are still catching up with a sufficient scientific coverage and evaluation of this issue. In other words, the area of reshoring is largely under-researched unlike its predecessor "offshoring" (e.g., Crinò, 2009;Lewin et al, 2009). This means that although literature on offshoring is widely available, reliable quality coverage on reshoring is in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Business and management science are still catching up with a sufficient scientific coverage and evaluation of this issue. In other words, the area of reshoring is largely under-researched unlike its predecessor "offshoring" (e.g., Crinò, 2009;Lewin et al, 2009). This means that although literature on offshoring is widely available, reliable quality coverage on reshoring is in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, it is related to the growing body of literature on the connections between international trade and the labor market, as reviewed by Klein et al (2003b) and Crino' (2009). Several studies have explored the impact of increasing foreign competition on net employment growth at the industry level.…”
mentioning
confidence: 99%
“…Most empirical studies on the consequences of offshoring focus largely on labor market issues-the level and skill composition of employment, and the level and structure of wages, which have been covered in several surveys [8], [9]. Although some studies have identified small negative effects on employment from offshoring, a consensus seems to be emerging that the effects are either broadly neutral or a small net gain in employment.…”
Section: World Of Labormentioning
confidence: 99%